Detection of Thermal Sublethal Injury in Escherichia coli via the Selective Medium Plating Technique: Mechanisms and Improvements - Espina, Laura; García-Gonzalo, Diego; Pagán, Rafael (Frontiers in Microbiology, 2016)
In food preservation, the selective medium plating technique (SMPT) is commonly used in order to detect and quantify the amount of sublethally injured cells in their bacterial cytoplasmic membranes after inimical treatments. From an applicative point of view, this information is of use in the synergistic combination of different preservation technologies, so that cells that are sublethally injured after one or more processes can end up being entirely inactivated by other hurdle(s). However, little work has been done to explain the reasons for the inability of sublethally injured cells to outgrow in selective agar media (containing the osmolyte NaCl as a selective agent), whereas they are able to grow in non-selective agar media. This research could contribute to explain this technique’s limits. In the present paper, the performance of SMPT on Escherichia coli cells after heat treatments is explored by applying different selective agents in the recovery media, using several mutants lacking factors involved in osmoregulation, and also by examining the integrity of the cytoplasmic membrane. In view of the results, the possibility of a specific toxic effect of Na+ as the main mechanism under SMPT is discarded, and the same level of sublethal injury is detected using KCl instead of NaCl. The synthesis of the osmoprotectant trehalose determined the maximum osmotolerance of intact cells to the selective agents, but was not crucial in the quantification of sublethal injury. Moreover, the extent of sublethal injury detected via SMPT was directly correlated with the physical loss of integrity of the cell membrane as measured with the propidium iodide-exclusion technique when that dye was added before thermal treatments. The present work confirms the adequacy of SMPT as a tool for detecting the occurrence and quantity of sublethally injured cells and thus, for efficiently designing combined preservation treatments. Additionally, we propose the combination of SMTP with flow cytometry and statistical analysis for a more rapid quantification of bacterial sublethal injury in a broad detection range (99.999% of the population).